x+1x−1 = abx+1x−1 = ab\frac{{x + 1}}{{x - 1}}{\text{ = }}\frac{a}{b} and 1−y1+y = ba," role="presentation">1−y1+y = ba,1−y1+y = ba,\frac{{1 - y}}{{1 + y}}{\text{ = }}\frac{b}{a}{\text{,}} then the value of x−y1+xy" role="presentation">x−y1+xyx−y1+xy\frac{{x - y}}{{1 + xy}} = ?" /> x+1x−1 = abx+1x−1 = ab\frac{{x + 1}}{{x - 1}}{\text{ = }}\frac{a}{b} and 1−y1+y = ba," role="presentation">1−y1+y = ba,1−y1+y = ba,\frac{{1 - y}}{{1 + y}}{\text{ = }}\frac{b}{a}{\text{,}} then the value of x−y1+xy" role="presentation">x−y1+xyx−y1+xy\frac{{x - y}}{{1 + xy}} = ?" /> x+1x−1 = abx+1x−1 = ab\frac{{x + 1}}{{x - 1}}{\text{ = }}\frac{a}{b} and 1−y1+y = ba," role="presentation">1−y1+y = ba,1−y1+y = ba,\frac{{1 - y}}{{1 + y}}{\text{ = }}\frac{b}{a}{\text{,}} then the value of x−y1+xy" role="presentation">x−y1+xyx−y1+xy\frac{{x - y}}{{1 + xy}} = ?" />
Post your Comments